A Single Intra-Articular Injection of Gel-200 for Treatment of Symptomatic Osteoarthritis of the Knee Is More Effective than Phosphate Buffered Saline at 6 Months: A Subgroup Analysis of a Multicenter, Randomized Controlled Trial. (October 2019) - Takamura, Junko; Seo, Takayuki; Strand, Vibeke
Objective: Many clinical trials of viscosupplementation have been conducted, although only the Gel-200 (primary) trial included a different patient population. A subgroup analysis of a multicenter, randomized controlled trial comparing the efficacy of single intra-articular injections of Gel-200 with phosphate buffered saline (PBS) was performed to demonstrate its benefit as treatment of osteoarthritis of the knee in a population similar to those of other reported trials of viscosupplementation. Design: The subgroup population was defined as patients in the intention-to-treat (ITT) population who met the specified criteria. Changes from baseline in Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores following treatment with Gel-200 or PBS were derived from a longitudinal model and treatment differences compared between groups at weeks 12 and 26, and over 26 weeks. Results: The subgroup included 311 subjects (152 Gel-200; 159 PBS). Mean improvements from baseline in WOMAC pain subscores in the Gel-200 over PBS groups were statistically significant at week 12 ( P = 0.031) and week 26 ( P = 0.019) . Treatment group differences in WOMAC stiffness and total scores were statistically significant at week 26 ( P = 0.023 and P = 0.036, respectively). Conclusions: The efficacy of Gel-200 following a single injection for knee osteoarthritis was demonstrated in WOMAC pain, stiffness, and total scores as well as clinically important improvements in pain at 26 weeks in this subset of patients with comparable characteristics to populations evaluated in other viscosupplementation treatment trials.